Peace Journalism in Framing Radical Islamic Issues in Bali - Amanda Gelgel, Ni Made Ras (ADDIN, 2020)
Nowadays, radical Islamic issues has becoming an international’s issues. News stories in media filled by this issue. Even local media also put this issue in their agenda, like local media in Bali Province. Since Bali bombing in 2002, people in Bali have their own trauma related to radical Islamic especially terrorism. Media have the power to shape people’s agenda, and to shape people’s perspective in any issues. So, local media in Bali have power to influence how people in Bali to see and understand the issue. The research’s quetions is how the media in Bali framing radical Islamic issues in 2018? Unit analysis in this research are Bali Post and Tribun Bali. Both of them have the highest traffic and the oldest newspaper in Bali. Research is using Entman’s Framing Method, which focus in how media selected issues and what aspect is highlighted by the media during 2018. The result is peace journalism has been practiced in framing radical issues in Bali.